Citizen Carter Dan Peningkatan Ekonomi Masyarakat Sebagai Upaya Pengentasan Kemiskinan - Muhammad Armoyu (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2014)
This article discusses the empowerment of the poor through social capital approach. The formulation of the specific problem is; (1) How does the social capital approach to improve the empowerment of the poor. (2) How is the effort done to solve the problem of poverty, but poverty persisted even show symptoms increase, although statistically likely to be reported decreased. Regardless of how the poverty statistics explores poverty reduction, poverty is in fact becoming increasingly worrisome problem. Study is a social science perspective. This study is an overview of poverty in Indonesia. Data were collected by means of describing and analyzed using descriptive analytical models. The results showed: (1) Poverty is a social problem that is becoming increasingly complex and complicated. (2) A lot of effort was made to solve the problem of poverty, but poverty persisted even show symptoms increase, although statistically likely to be reported decreased.